Multiple HPV infections in female sex workers in Western Kenya: implications for prophylactic vaccines within this sub population - Sonia Menon; Davy van den Broeck; Rodolfo Rossi; Emilomo Ogbe; Hillary Mabeya (Infectious Agents and Cancer, 2017)
Abstract Background Whilst the imputed role of High Risk (HR) HPV infection in the development of cervical lesions and cancer has been established, the high number of HPV genotypes that Female Sex workers (FSW) harbour warrants that the synergistic effects of potential HR (pHR) and HR HPV genotypes be elucidated to assess the potential impact of prophylactic vaccines. This population in Kenya also harbours a number of other vaginal infections and STIs, including bacterial vaginosis (BV), trichomonas vaginalis (TV) and candida spp. The aims of this cross-sectional analysis in Kenya are to explore the epidemiology of abnormal cytology and the pairing of pHR/HPV genotypes in HIV-negative and HIV-infected FSW. Methods A cross-sectional study design of 616 FSW from Western Kenya aged between 18 and 61 years during 2009–2015 using a peer recruitment sampling strategy. Results Of the 599 FSW who underwent cytological examination, 87 had abnormal cytology (14.5%; 95% CI: 12.0–17.6%). A combined prevalence of HPV16 and 18 (29.6%; 95% CI: 22.2–37.8%) was observed in abnormal cytology. HPV 53 and 51 were the most observed pairing in FSW with abnormal cytology. Significant adjusted associations were found between abnormal cytology and TV (aOR: 30; 95% CI: 14.1–62.9), multiple HR HPV (aOR: 3.7; 95% CI: 1.9–7.3), HPV 51 (aOR 3.7; 95% CI 1.6–8.6) and HPV 52 (aOR 6.1; 95% CI: 2.8–13.3). Conclusion HPV 51 and 52 were independently associated with abnormal cervical cytology in both HIV negative/positive FSW. The strong association between TV and cervical dysplasia and the high percentage of FSW harbouring more than one STI underscore the need for enhanced STI management within the framework of cervical cancer prevention.